2008
DOI: 10.1590/s1678-77572008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between margin fit and microleakage in complete crowns cemented with three luting agents

Abstract: Microleakage can be related to margin misfit. Also, traditional microleakage techniques are time-consuming. This study evaluated the existence of correlation between in vitro margin fit and a new microleakage technique for complete crowns cemented with 3 different luting agents. Thirty human premolars were prepared for full-coverage crowns with a convergence angle of 6 degrees, chamfer margin of 1.2 mm circumferentially, and occlusal reduction of 1.5 mm. Ni-Cr cast crowns were cemented with either zinc phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 38 publications
7
52
1
1
Order By: Relevance
“…The assessment of the marginal adaptation was performed on extracted human molars which have been also used in previous studies [15,45] because their modulus of elasticity, bonding characteristics, thermal conductivity and strength are closer to the clinical situation rather than those of metal, plastic and animal teeth. The teeth were stored in thymol solution to prevent them from drying out and thereby becoming brittle, and inhibit the microbial activity [6].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the marginal adaptation was performed on extracted human molars which have been also used in previous studies [15,45] because their modulus of elasticity, bonding characteristics, thermal conductivity and strength are closer to the clinical situation rather than those of metal, plastic and animal teeth. The teeth were stored in thymol solution to prevent them from drying out and thereby becoming brittle, and inhibit the microbial activity [6].…”
Section: Discussionmentioning
confidence: 99%
“…31 The significance level was set at a = 0.05 for all statistical tests. [29][30][31] All data analyses were made with SPSS/PC+ v.17.0 (SPSS Inc., Chicago, IL, USA) statistical software.…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 survey by Clinician's Report found that 55% of dentists use RMGI cement and 39% of dentists use a resin cement for zirconia crowns . Several in vitro studies have shown increased microleakage, as measured by dye penetration, around margins of crowns cemented with RMGI cements than resin cements . In contrast, an in vitro study reported less bacterial microleakage in crowns cemented with RMGI cement than resin cement…”
Section: Introductionmentioning
confidence: 97%
“…An i n vitro study found more adverse effects on surface roughness of resin‐based restorative materials using magnetostrictive ultrasonic scalers than sonic scalers . Piezoelectric ultrasonic scalers are clinically favorable due to their quieter operation, smaller tips and handpieces, and ease of use . It is possible that the vibrational forces produced by piezoelectric ultrasonic scalers may disrupt the bond formed at the crown margin.…”
Section: Introductionmentioning
confidence: 99%